Jawi generator software implemented on single board computer (SBC) - Noor Shalasiah Osman (School of Computer and Communication Engineering, 2011)
The research basically is to design and develop Jawi Generator Software in personal computer (PC) and implemented in TS-7395 SBC board. This system will generate the format of writing Jawi scripts for the users who do not have the basic knowledge at all. From this system, the user will know and learn the type of Jawi script in provided modules options which are Isolated, Initial, Medial, Final and Combine.